Sexual orientation and gender identity disparities in co-occurring depressive symptoms and probable substance use disorders in a national cohort of young adults. (June 2021) - Felner, Jennifer K.; Haley, Sean J.; Jun, Hee-Jin; Wisdom, Jennifer P.; Katuska, Laura; Corliss, Heather L.
Highlights: Sexual minorities had greater odds of co-occurring depressive symptoms and SUDs. Disparities disproportionately impacted sexual minorities assigned female at birth. Gender minorities had more co-occurring depressive symptoms and alcohol disorders. Abstract: This study examined sexual orientation and gender identity differences in co-occurring depressive symptoms and substance use disorders (SUDs) among young adults in the Growing Up Today Study national cohort (n = 12, 347; ages 20–35; 93% non-Hispanic white). Self-administered questionnaires assessed recent co-occurring depressive symptoms and probable nicotine dependence, alcohol use disorder, and drug use disorder. Multinomial logistic regressions with generalized estimating equations quantified differences in prevalences of depressive symptoms only, SUDs only, and co-occurrence, among sexual minorities (mostly heterosexual; lesbian, gay, and bisexual [LGB]) compared to completely heterosexual participants, and gender minorities compared to cisgender participants. Analyses stratified by sex assigned at birth revealed sexual minorities evidenced greater odds of co-occurrence than their completely heterosexual counterparts (assigned female AORs: 3.11–9.80, ps < 0.0001; assigned male AORs: 2.90–4.87, ps < 0.001). Sexual orientation differences in co-occurrence were pronounced among LGB participants assigned female at birth who evidenced nearly 10 times the odds of co-occurring depressive symptoms with nicotine dependence and drug use disorders than did heterosexual participants assigned female at birth. Relationships between gender identity and co-occurrence were generally weaker, possibly due to low power. Gender minorities assigned male at birth, however, evidenced greater odds of co-occurring depressive symptoms and alcohol use disorders (AOR 2.75, p = 0.013) than their cisgender counterparts. This study adds to the limited research quantifying sexual orientation or gender identity differences in recent co-occurring depressive symptoms and SUDs among young adults and suggests sexual and gender minority young adults should be prioritized in prevention and treatment of co-occurring depression and SUDs.